Emergency depopulation of chicken farms during an Avian Influenza (AI) outbreak (Experimental testing and modelling for establishing design parameters) - Liang, Kang Wei (2016)
Avian Influenza (AI), commonly referred to as bird flu, is an infectious viral disease of birds. Most avian influenza viruses do not infect humans; however some such as A(H5N1) and A(H7N9), have caused serious infections in people [1]. Human infections occur when enough virus gets into a person’s eyes, nose or mouth, or is inhaled. The Agri-Food & Veterinary Authority (AVA) of Singapore has precautionary measures in place to keep the disease out of Singapore. It requires the depopulation of all live poultry within 24 hours after confirmation of an outbreak. Local poultry farms currently extract laying hens by hand. This method is time-consuming, tedious and strenuous even for experienced farm workers. In the event of an emergency depopulation exercise, only AVA personnel are allowed to depopulate the laying hens. As such, the risk of injury, movement restriction, and fatigue levels may be increased. The aim of this project is to devise a solution that will provide a much faster way to depopulate the chicken cages. A working prototype will be designed and built, and tested for proof of concept. A concept study to compare the previous final year student’s hen-containment model and non-containment models found that non-containment is the better option as it minimizes fatigue and stress from repeated lifting of the hens’ weight. The option is also lighter and cost-effective as a simpler design and less materials are required. The non-containment model, HenHerder, which is fully mechanical, aims to remove all hen occupants of one cage in a single action.